Queer histories and the politics of policing - Russell, Emma K. (Queering criminology and criminal justice, 2020)
"Based on original empirical research in Australia, this book presents a detailed analysis of the political complexities, compromises, and investments that underpin LGBT efforts to achieve sexual rights and protections"--